PENGARUH INSENTIF PAJAK, KESADARAN WAJIB PAJAK, SANKSI PAJAK DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Abdi Pradnyani, N L P Norma Dewi; Sari, Putu Indrika; Suprapto, P Adi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022DO - 10.24843/EEB.2022.v11.i01.p09, 2022)
This study aims to examine the effect of tax incentives, taxpayer awareness, tax sanctions, and the application of e-filling on MSMEs taxpayer compliance. This study is a quantitative study using primary data obtained from the answers to questionnaires distributed to respondents and measured using a likert scale. The population in this study are MSMEs taxpayers registered at the KPP Pratama Gianyar. Determination of the sample in this study using purposive sampling technique with a sample of 100 people obtained through the slovin formula. The variables in this study were tested using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach using the SmartPLS 3.0 application. The results of the study indicate that tax incentives, taxpayer awareness, tax sanctions, and the application of e-filling have a positive and significant impact on MSMEs tax compliance at the KPP Pratama Gianyar